2016
DOI: 10.1089/jpm.2015.0120
|View full text |Cite
|
Sign up to set email alerts
|

ICU versus Non-ICU Hospital Death: Family Member Complicated Grief, Posttraumatic Stress, and Depressive Symptoms

Abstract: Psychological distress of family members did not differ by hospital setting, but the most distressing experiences encountered at end of life in each setting highlight potentially unique interventions to reduce distress post-bereavement for family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 29 publications
3
41
1
3
Order By: Relevance
“…A recent study found that these symptoms in family members persisted 3 months after ICU discharge while they decreased in patients (Fumis 2015). PICS family, should therefore be assessed in the family members of patients who survive ICU treatment (Probst et al 2016). ICU patients' family members are prone to shame feelings, especially when having low levels of education and living with the patient (Koulouras et al 2017).…”
Section: Word Count: Introductionmentioning
confidence: 99%
“…A recent study found that these symptoms in family members persisted 3 months after ICU discharge while they decreased in patients (Fumis 2015). PICS family, should therefore be assessed in the family members of patients who survive ICU treatment (Probst et al 2016). ICU patients' family members are prone to shame feelings, especially when having low levels of education and living with the patient (Koulouras et al 2017).…”
Section: Word Count: Introductionmentioning
confidence: 99%
“…10, nº 2, pp. 211-248 Probst, 2016). Como señala Moriconi (2020), el duelo por la muerte de un familiar en una UCI se relaciona con una peor aceptación de la pérdida y con síntomas compatibles con duelo complicado (5% -52%), trastorno de estrés postraumático (TEPT) (14% -50%) y depresión (18% -27%).…”
Section: Comunicación De Malas Noticias Duelo Y Covid-19unclassified
“…Dessa forma, o cuidado dos familiares é uma das partes mais importantes do cuidado global dos pacientes internados, principalmente por que estes, na maioria das vezes, estão sedados e impossibilitados de tomar decisões (Moritz et al, 2011;Probst, Gustin, Goodman, Lorenz, & Wells-Di Gregorio, 2016). No âmbito dessas considerações, neste trabalho, buscou-se discutir percepções e recursos emocionais dos familiares diante da terminalidade.…”
Section: La Muerte En Escena: La Familia Ante Una Situación Terminal unclassified